Mineralogical investigation and mineral processing of iron ore from the Skines area (Chania – West Crete) - Trichos, D.; Alevizos, G.; Stratakis, A.; Petrakis, E.; Galetakis, M. (Bulletin of the Geological Society of Greece, 2013)
Several iron ore occurrences are placed in the island of Crete and especially in the prefectures of Chania and Rethymno (Western Crete), some of which have been occasionally exploited. The aim of the present study is the mineralogical examination and the investigation of mineral processing potential of an iron ore occurrence located in the area of Skines village near to the city of Chania. The investigated iron ore occurrence form lenses which are placed within the contact of the phyllitequartzite of Phyllite-Quarzite-Series (PQS) of Crete and the overlaid limestones. The major minerals of the iron ore are goethite, hematite and quartz, while the less common are muscovite, lepidocrocite, gibbsite, talc and pyrite. The ore microscopy exanimation indicated that an extended epigenetic ferruginisation process has taken place. In general, mineral processing by using heavy liquid and magnetic separation did not give satisfactory results, except for the size fraction -1+0,250 mm of the heavy liquid and the magnetic products of size ftactions -8+4 mm, -4+1 mm and -1+0,250 mm. Ore microscopy examination of the different size fractions indicated that the difficulties in mineral processing are closely related to the ore liberation.